THE FUNCTIONS OF HUMOROUS DISCOURSE IN MIND YOUR LANGUAGE - Romadlani, Muhammad Masqotul Imam; Wijana, I Dewa Putu (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2021)
The primary purpose of this study is to reveal the function of humorous discourse identified in the Mind Your Language situation comedy series. The researcher adopted a descriptive qualitative approach to complete this humor research. The data were obtained from the script of that sitcom. The function of humorous discourse found in that sitcom was then classified based on Hay's framework, which divides the function of humor into three main functions: the function of solidarity, the function of power, and the function of psychology. The findings demonstrate that teasing and satire humor inÂ Mind Your LanguageÂ sitcom are utilized to express solidarity. Meanwhile, humorous discourses that trigger conflict, harm, threaten others or show disagreement are created to express the function of power. Furthermore, humorous discourse to gain an advantage, protect oneself, entertain, or boast is used to express the function of psychology. The context of the conversation given is highly significant in identifying the function of humor. The same humorous discourse provided in different contexts potentially implicates different functions of humor which indicates that determining the function of humor is heavily grounded by the context.Â